Carbon Storage in Seagrass in The East and North Coastal Waters of Bintan Island - Syahbana Advani Alsha; Andi Zulfikar; Winny Retna Melani (Universitas Airlangga, 2026)
Seagrass has the ability to store carbon by utilizing CO2 to be used as a photosynthesis component which has the potential as blue carbon. This research was aimed to determine density, and biomass in the East and North Coastal Waters of Bintan Island; determine the carbon storage contained in seagrass in the East and North Coastal Waters of Bintan Island; and determine the relationship between density, biomass, and carbon storage in seagrasses in the East and North Coastal Waters of Bintan Island. The research was conducted in Teluk Bakau, Malang Rapat, Berakit, and Pengudang from August 2024 to May 2025. The tools and materials used were 50 × 50 cm2, oven, muffle furnace, shieve net, underwater camera, plastic bag, seagrass samples, and substrate samples. The research procedures was used systematic random sampling method and the sampling design used in determining sampling points was a nested hierarchical design. The method of calculating the value of carbon storage in seagrasses used the Walkley and Black method. The data analysis was carried out by calculating the value of density, biomass; then calculating the value of carbon storage in seagrasses, and testing the relationship between density, biomass, and carbon storage in seagrasses. Density in the eastern region ranged from 284-577 shoot/m2 and in the northern region ranged from 107-816 shoot/m2. Biomass in the eastern region ranged from 39,31-82,99 gr/m2 and in the northern region ranged from 19,39-138,55 gr/m2. Carbon storage in the eastern region ranged from 27,46-31,03% and in the northern region ranged from 23,93-28,30%. The results of the correlation test show that density has a moderate relationship and is directly proportional to biomass with a correlation value of 0.51; density has a very weak relationship and is inversely proportional to carbon storage with a value of -0.09; and biomass has a weak relationship and is inversely proportional to carbon storage with a value of -0.24.